IDSL (Inexpensive Device for Sea Level) performance analysis for tews (Tsunami Early Warning System) in Sadeng fisheries port. Issue 1 (October 2021) - Novianto, Dian; Husrin, Semeidi; Nugroho, Dwiyoga; Bramawanto, Rikha; Setiawan, Agus; Permana, Sofiyan M.; Sufyan, Agus; Sianturi, Daud SA; Daniel, Donal; Ridlo Suhelmi, Ifan; Fauzah, Syarifah
Abstract: Inexpensive Device for Sea Level Monitoring or IDSL is one of TEWS devices operating in Indonesia for more than two years, monitoring real-time on a 24/7 sea level and providing email, SMS alerts, CCTV images, and information about a potential event of a tsunami. This paper aims to analyze the device's performance at Sadeng Fisheries Port based on critical parameters for tsunami early warning systems such as data quality, latency time, the quality of CCTV images, and the release of warning capabilities. The results show that the tidal range at spring tide is about 3.19 m, in line with BIG tidal station data. These data also indicate that the minimum tide height is 0.06 m and the maximum tide height is 3.25 m. Performance results show a total data gap of 1717 data gaps with a minimum gap of 10 seconds and a maximum gap for two days of 9 hours, with latency intervals dominated by values less than 30 seconds. However, consist eight extreme latencies in the observation period are associated with internet quotas and technical interference. For the quality of CCTV cameras, good quality images contributed to about 84, 85%. Although there are many interferences from GSM signals and vessel activity below the sensors, the overall performance of this device has shown high reliability to strengthen the existing tsunami early warning system in the South of Java and Indonesia.